การจัดการการท่องเที่ยวโดยชุมขนตามปรัชญาของเศรษฐกิจพอเพียงชุมชนบ้านหัวเขาจีน อำเภอปากท่อ จังหวัดราชบุรี - แก้วมณี, จิราภรณ์ (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 26 No 2 (2558): Academic Services Journal, Prince of Songkla University, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาระดับการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาของเศรษฐกิจพอเพียง 2) ศึกษาระดับการปฏิบัติที่ดีในการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาของเศรษฐกิจพอเพียง 3) ศึกษาแนวทางในการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาของเศรษฐกิจพอเพียง วิธีการวิจัยเป็นแบบผสมผสานวิธี ด้วยการเก็บรวบรวมข้อมูลทั้งเชิงปริมาณและเชิงคุณภาพ จากกลุ่มตัวอย่าง เป็นหัวหน้าครัวเรือนจำนวน 108 หลังคาเรือน โดยใช้การสุ่มตัวอย่างแบบง่าย เครื่องมือที่ใช้ในการวิจัยครั้งนี้ คือ แบบสอบถาม จากนั้นศึกษาในงานวิจัยเชิงคุณภาพ โดยการสัมภาษณ์เชิงลึกเกี่ยวกับการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาของเศรษฐกิจพอเพียงของชุมชนกับผู้เกี่ยวข้องกับการท่องเที่ยวในชุมชน จำนวน 9 คน และการสนทนากลุ่มเกี่ยวกับการปฏิบัติที่ดีในการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาของเศรษฐกิจพอเพียงชุมชนกับผู้เกี่ยวข้องกับการท่องเที่ยวในชุมชน จำนวน 10 คน โดยการคัดเลือกกลุ่มตัวอย่างแบบเจาะจง สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ การแจกแจงความถี่ ร้อยละ ค่าเฉลี่ยและส่วนเบี่ยงเบนมาตรฐาน จากนั้นนำแบบสอบถามมาตรวจความถูกต้องและความครบถ้วนของข้อมูลแล้วนำไปประมวลผลการวิเคราะห์ข้อมูลโดยใช้โปรแกรมสำเร็จรูปและใช้การวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1. ระดับการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาของเศรษฐกิจพอเพียงชุมชนบ้านหัวเขาจีน พบว่า ทุกด้านอยู่ในระดับมาก เรียงลำดับ ดังนี้ ด้านทรัพยากรธรรมชาติและวัฒนธรรมมีคะแนนเฉลี่ยสูงที่สุด รองลงมาเป็นด้านการเรียนรู้ และด้านที่ตํ่าที่สุด คือ ด้านการจัดการ 2. ระดับการปฏิบัติที่ดีในการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาเศรษฐกิจพอเพียงชุมชนบ้านหัวเขาจีน พบว่า ทุกด้านอยู่ระดับมาก ด้านที่มีระดับความคิดเห็นมากที่สุด คือด้านการท่องเที่ยวตั้งอยู่บนพื้นฐานเดิมของชุมชนไทยทรงดำ รองลงมาเป็นด้านการท่องเที่ยวตั้งอยู่บนภูมิสังคม และด้านที่ตํ่าที่สุด คือ ด้านการท่องเที่ยวยึดหลักความคุ้มค่ามากกว่าคุ้มทุน 3. แนวทางในการจัดการการท่องเที่ยวโดยชุมชนตามปรัชญาของเศรษฐกิจพอเพียงชุมชนบ้านหัวเขาจีน พบว่า 1) ชุมชนบ้านหัวเขาจีนมีทุนทางวัฒนธรรม ทุนทางภูมิปัญญาชาวบ้านเป็นเอกลักษณ์ไทยทรงดำแล้วนั้น หากได้ความร่วมมือทั้งภาครัฐและภาคเอกชนเข้ามาช่วยจัดการวางแผนดำเนินงานร่วมกับผู้นำชุมชนจะทำให้การท่องเที่ยวโดยชุมชนนั้นก้าวหน้าได้มาก 2) ชุมชนมีการรวมกลุ่มอาชีพกันด้วยความสมัครใจและมีหลากหลายกลุ่มอาชีพ ได้รับรางวัลมากมายหากหน่วยงานที่เกี่ยวข้องสนับสนุนงบประมาณในการรวมกลุ่มอาชีพของชุมชนจะเป็นการพัฒนาฝีมือแรงงาน พัฒนาสินค้าให้ส่งออกได้จำนวนมาก 3) หน่วยงานที่เกี่ยวข้องเข้ามาช่วยเหลือทำป้ายบอกทาง การประชาสัมพันธ์ให้รู้จักแก่บุคคลภายนอกมากยิ่งขึ้น คำสำคัญ: การจัดการการท่องเที่ยวโดยชุมชน, ปรัชญาของเศรษฐกิจพอเพียง   This research aimed 1) to investigate community-based tourism management in accordance with the philosophy of sufficiency economy, 2) to explore good practices of community-based tourism management in congruent with the philosophy of sufficiency economy, and 3) to study guidelines on community-based tourism management in congruent with the philosophy of sufficiency economy. This was a mixed-method research collecting. This was both quantitative and qualitative data from 108 householders using a simple random sampling. A questionnaire was used as an instrument. With regard to the qualitative data collection, utilizing a purposive sampling technique, an in-depth interview from 9 householders relating to the community-based tourism management in accordance with the philosophy of sufficiency economy and a focus group discussion concerning good practices of community-based tourism management in congruent with the philosophy of sufficiency economy with 10 concerned people to community’s tourism management were applied. Statistics used in data analysis were distribution of frequency, percentage, mean, and standard deviation. After checking the correctness and completeness of the data, the questionnaire was analyzed by means of using a statistical program package, and the qualitative data was analyzed by means of using content analysis technique. The study revealed that: 1. All aspects of the community-based tourism management in congruent with the philosophy of sufficiency economy of Baan Hua Khao Jean Community were found at high levels. Natural resources and culture aspects were found at the highest level, followed by learning aspect. The lowest one was management aspect. 2. With regard to the good practices of the community-based tourism management in congruent with the philosophy of sufficiency economy of Baan Hua Khao Jean, the study revealed that all aspects were found at high levels. The aspect showing the highest opinion was Thai Song Dam Community-based tourism, followed by tourism geosocial. The lowest opinion was tourism that bases on being worthwhile more than breakeven. 3. In accordance with the guidelines on the community-based tourism management in congruent with the philosophy of sufficiency economy, the study found that 1) besides, Baan Hua Khao Jean Community has their cultural capital and local wisdom capital with the Thai Song Dam identity, the community-based tourism management will much succeed if there was cooperation between the government, private sectors and local community’s leaders in managing the community-based tourism. 2) There was voluntarily a wide range of occupations grouping in the community which received numerous awards, if concerned agencies give financial support to the group, it can develop the labor skills and improve local product that can be exported. 3) Concerned agencies should provide direction and public relation to outsiders. Keywords: community-based tourism management, philosophy of sufficiency economy